Characteristic of Urinary Tract Stones Patient in Sido Waras General Hospital Mojokerto - Kristian Mohamad Daniputra; Antono Pratanu (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2021)
Introduction & Objectives: Urinary tract stones had been discovered since ancient Egyptian period. In eighteenth century, a Russian scientist H.C.G von Struve discovers struvit stone in which the formation of the stone is initiated by urinary tract infection. Prevalence of kidney stone disease in Indonesia is 0,6% in 2013 and in the United States, incidence of kidney stone disease is 116/100.000 people in 2000. The objective of this research is to determine the characteristic of urinary tract stone patients treated in Sido Waras General Hospital Mojokerto, East Java. Material & Method: The design of this research is descriptive study. The inclusion criteria is all new cases of urinary tract stone treated in Sido Waras General Hospital between 2017 until 2018. All clinical data regarding urinary tract stone disease is obtained from medical record retrospectively. Results: There are 285 new cases of urinary tract stone treated in Sido Waras General Hospital Mojokerto in 2 years, in which 236 cases (83%) are male and 49 cases (17%) are female. Most of urinary tract stone patients are classified in 40-60 years old group with 197 cases in two years. The most common case of urinary tract stone is kidney stone with 147 cases (51%). Open surgery is the most common management which is done for urinary tract stone disease in two years (52%). Based on comorbid disease, there are 120 urinary tract stone patient (42%) suffering hypertension and 84 urinary tract stone patients (29%) suffering diabetes mellitus. Conclusion: The incidence of urinary tract stone in Sido Waras General Hospital is 285 cases. Urinary tract stones are more common in male, with male to female ratio 4:1. The majority of cases are kidney stone.